1. The problem statement, all variables and given/known data Verify that the given function is in the kernel of L. y(x)=x-2 L = x2D2 + 2xD - 2 2. Relevant equations 3. The attempt at a solution I took the first and 2nd derivative of y(x), and got y'(x)= -2x-3 y''(x)= 6x-4 Then plugged it into L (and a little simplifying) and got L(y) = 6x-2+2x-1-2 I think I'm supposed to plug it in, and verify that it's equal to zero, but it's not coming out right. Any obvious mistakes? Or wrong direction all together?